2016
DOI: 10.1002/jbm.b.33686
|View full text |Cite
|
Sign up to set email alerts
|

Time course of surface characteristics of alkali‐ and heat‐treated titanium dental implants during vacuum storage

Abstract: Current efforts to shorten the healing times of life-long dental implants and prevent their fouling by organic impurities have focused on using surface-modification treatments and alternative packaging, respectively. In this study, we investigated the time course of the surface characteristics, including the wettability, a protein-adsorption and apatite-formation abilities, of alkali- and heat-treated (AH-treated) Ti samples during storage in vacuum over a period of 52 weeks. The AH treatment resulted in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Increase of surface activity is achieved by a three-step mechanism: Removal of hydrocarbon contaminants; induced surface hydrophilicity; change of the surface charge from negative to positive. Medical devices would probably be stored for a very long time before usage, up to 5 years [ 185 ], therefore removal of atmospheric contaminants is a priority. This will be discussed deeply later in Section 4.1 .…”
Section: How the Characteristics Of Titanium Based Biomaterials Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Increase of surface activity is achieved by a three-step mechanism: Removal of hydrocarbon contaminants; induced surface hydrophilicity; change of the surface charge from negative to positive. Medical devices would probably be stored for a very long time before usage, up to 5 years [ 185 ], therefore removal of atmospheric contaminants is a priority. This will be discussed deeply later in Section 4.1 .…”
Section: How the Characteristics Of Titanium Based Biomaterials Inmentioning
confidence: 99%
“…Biological properties of titanium need to be preserved even through the long-lasting storage of the biomedical devices, up to five years. Implants and dental screw are usually enclosed in a sterile gas-permeable packaging, which keeps the contents sterile but allows contamination of the surfaces by the carbonaceous organic impurities in the atmosphere [ 185 , 200 ]. Very recent molecular dynamic studies performed by Wu et al [ 201 ] demonstrated that carbon contaminants expose C-H bonds, thus greatly reducing surface polarity and dipole–dipole interactions with proteins.…”
Section: External Parameters Affecting Protein Adsorption On Titanmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing preferable storage media, Wennerberg et al [62] suggested that, unlike that of pure water, wet storage in aqueous solution reorganized the TiO 2 nanostructures. Kamo et al [63] suggested that the use of gas-barrier (vacuum) packaging during shelf storage resulted in better wettability, and hence, greater protein adsorption compared with the use of a gas-permeable container.…”
Section: Titanium Surface Contaminationmentioning
confidence: 99%
“…Commercially available implants are inevitably contaminated with hydrocarbons in their packaging, 1 with an average percentage ranging from 17.9% to 76.5%. 2 Increase in carbon content decreases the hydrophilicity, thus increasing the chances of implant failure.…”
Section: Introductionmentioning
confidence: 99%